EFEKTIVITAS PROBLEM BASED LEARNING DAN INQUIRY TERHADAP KEMAMPUAN BACK ROLL SMP NEGERI 7 PONTIANAK - Albar, Lutfi Abdulah; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem of this research was the students who have difficulty in doing back roll movements. Thisstudy aims to find the right learning model used for back roll learning. The method in this study uses anexperimental method with shape true experimental design. The sampel in this study amounted to 42students. Data retrieval techniques using direct observation techniques. The instrument used is the backroll performance test rubric. Data analysis using t test analysis and effect size test. Based on thecalculation of the data obtained the results of the ability to back roll with the problem based learningmodel dan inquiry with t count and t tabel or 5.607 > 2.191 that is, there are differences in effectivenessbetween models problem based learning and inquiry to ability to back roll class studentsVII at SMP N 7Pontianak. As for results of the effect size test the result is 0.40, thi means that the problem basedlearning and inquiry model has a moderated influence on tha ability of the back roll.Key word: Problem Based Learning, Inquiry, Back Roll